Multiple Roles for the Ess1 Prolyl Isomerase in the RNA Polymerase II Transcription Cycle - Ma, Zhuo (American Society for Microbiology, 2012)
The Ess1 prolyl isomerase in Saccharomyces cerevisiae regulates RNA polymerase II (pol II) by isomerizing peptide bonds within the pol II carboxy-terminal domain (CTD) heptapeptide repeat (YSPTSPS). Ess1 preferentially targets the Ser5-Pro6 bond when Ser5 is phosphorylated. Conformational changes in the CTD induced by Ess1 control the recruitment of essential cofactors to the pol II complex and may facilitate the ordered transition between initiation, elongation, termination, and RNA processing. Here, we show that Ess1 associates with the phospho-Ser5 form of polymerase in vivo, is present along the entire length of coding genes, and is critical for regulating the phosphorylation of Ser7 within the CTD. In addition, Ess1 represses the initiation of cryptic unstable transcripts (CUTs) and is required for efficient termination of mRNA transcription. Analysis using strains lacking nonsense-mediated decay suggests that as many as half of all yeast genes depend on Ess1 for efficient termination. Finally, we show that Ess1 is required for trimethylation of histone H3 lysine 4 (H3K4). Thus, Ess1 has direct effects on RNA polymerase transcription by controlling cofactor binding via conformationally induced changes in the CTD and indirect effects by influencing chromatin modification.